Understanding Referral Patterns for Bone Mineral Density Testing among Family Physicians: A Qualitative Descriptive Study. (19th January 2016) - Munce, Sarah E. P.; Allin, Sonya; Carlin, Leslie; Sale, Joanna; Hawker, Gillian; Kim, Sandra; Butt, Debra A.; Polidoulis, Irene; Tu, Karen; Jaglal, Susan B.
Abstract : Introduction . Evidence of inappropriate bone mineral density (BMD) testing has been identified in terms of overtesting in low risk women and undertesting among patients at high risk. In light of these phenomena, the objective of this study was to understand the referral patterns for BMD testing among Ontario's family physicians (FPs). Methods . A qualitative descriptive approach was adopted. Twenty-two FPs took part in a semi-structured interview lasting approximately 30 minutes. An inductive thematic analysis was performed on the transcribed data in order to understand the referral patterns for BMD testing. Results . We identified a lack of clarity about screening for osteoporosis with a tendency for baseline BMD testing in healthy, postmenopausal women and a lack of clarity on the appropriate age for screening for men in particular. A lack of clarity on appropriate intervals for follow-up testing was also described. Conclusions . These findings lend support to what has been documented at the population level suggesting a tendency among FPs to refer menopausal women (at low risk). Emphasis on referral of high-risk groups as well as men and further clarification and education on the appropriate intervals for follow-up testing is warranted.